Nutritional Knowledge and Eating Habits among IT Undergraduates of Kathmandu Metropolitan City (Janaki Medical College Journal of Medical Science, 2023)
Background & Objectives: Undergraduate students can be almost of any age, but majority of the students are in their late teens and early twenties. It is the time of physical and emotional changes as the body matures and the mind becomes more curios and independent and there is an increased desire for knowledge. Thus, the aim of the study was to access the nutritional knowledge and eating Habits among Information technology (IT) undergraduates of Kathmandu Metropolitan City.Material and Methods: This was descriptive cross-sectional study based in Kathmandu Metropolitan City. A total of 422 samples were taken and the study population was IT undergraduates. Chi-square test was used to determine the statistical relationship between dependent and independent variables.Results: The respondent's average age was 20.19.  One of the primary sources of nutritional knowledge was education. Nearly all of the respondents thought that fast food and junk food tasted good. The main drivers of junk food and fast food consumption were convenience and flavor. A statistical association existed between the amount spent each week on fast food and junk food and the amount of monthly pocket money. The vast majority of respondents had poor eating habits and insufficient nutritional knowledge. While the majority of students skipped their meals, three-fourths of respondents ate three meals a day, with breakfast being skipped the most frequently, followed by lunch, dinner, and snacks.Conclusion: The study concluded that the vast majority of respondents had poor eating habits and insufficient nutritional knowledge. The primary reason of meal skipping was irregular college hours. It requires constant and long-term effort in personal, parental and college policy in order to make healthy eating a lifestyle must begin from the earliest age possible.